ENVIRONMENTAL AND OCCUPATIONAL HEALTH AND SAFETY CONSIDERATIONS IN HEAP LEACHING: A CRITICAL ANALYSIS OF RISKS AND MANAGEMENT IN THE MINING INDUSTRY - KÜLEKÇİ, GÖKHAN; UÇAK, Gül (Göbeklitepe Medical Science Journal, 2024)
Mining is an important industry that must be considered for its environmental impacts and occupational health and safety. This article aims to focus on heap leaching, a process used in mining, from an environmental and occupational safety perspective. Firstly, the article provides a general framework for mining operations. Within this framework, steps such as the exploration of mining sites, mining engineering and planning, mining activities, crushing and grinding, separation and beneficiation, concentrate and metal production, waste management and environmental protection, occupational safety, health, and rehabilitation are addressed. Heap leaching is commonly used in the beneficiation of valuable metals, and its basic principles are explained. Lastly, the environmental and occupational health and safety issues that may arise during the heap leaching process are addressed. These issues include exposure to chemicals, accident risks, waste management, worker training, and awareness. Additionally, the importance of occupational health and safety is emphasized by referencing cyanide accidents and their consequences worldwide. In conclusion, environmental and occupational health and safety issues related to heap leaching in the mining industry are a serious concern. Strict regulations and safety measures must be implemented to effectively manage these issues. This article will serve as an important resource for raising awareness and fostering discussion about heap leaching in the mining industry.